Utilizing AI and Blockchain for Business Innovation in Digital Strategy - Sunarya, Po Abas; Yusup, Muhamad; Fae, Nahlie (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2026)
In the rapidly evolving digital era, businesses are confronted with the challenge of adapting to fast paced technological changes. Innovative technologies such as Artificial Intelligence (AI) and Blockchain have emerged as solutions that can accelerate business transformation. AI offers data analytics and automation capabilities that enhance operational efficiency, while Blockchain provides the transparency and security required in digital business transactions. This study aims to explore how AI and Blockchain can be leveraged to drive innovation in business strategies and strengthen competitive advantage in an increasingly digital market. The research employs a literature review approach to examine the implementation of AI and Blockchain across various industrial sectors. For example, in the e-commerce sector, major companies such as Amazon and Alibaba have implemented AI to improve customer experience through more accurate product recommendations. Additionally, Blockchain has been utilized by Walmart to enhance supply chain transparency, enabling product traceability from suppliers to consumers. The collected data were analyzed to understand the impact of these technologies on business models and the innovations adopted by companies. The findings indicate that AI accelerates decision making processes and enables personalized customer services, while Blockchain helps establish a more transparent and efficient business ecosystem. Both technologies contribute to the development of stronger and more adaptive digital business models. The implementation of AI and Blockchain in business strategies has proven to enhance innovation, improve operational efficiency, and reinforce competitive advantage. Therefore, adopting these technologies becomes a key factor in achieving success in digitally driven businesses.